The status of bridge principles in applied econometrics - Bernt P. Stigum (Econometrics, 2016)
The paper begins with a figurative representation of the contrast between present-day and formal applied econometrics. An explication of the status of bridge principles in applied econometrics follows. To illustrate the concepts used in the explication, the paper presents a simultaneous-equation model of the equilibrium configurations of a perfectly competitive commodity market. With artificially generated data I carry out two empirical analyses of such a market that contrast the prescriptions of formal econometrics in the tradition of Ragnar Frisch with the commands of present-day econometrics in the tradition of Trygve Haavelmo. At the end I demonstrate that the bridge principles I use in the formal-econometric analysis are valid in the Real World-that is in the world in which my data reside.
Keywords: A12; A19; B23; B41; C01; C18; C30; C49; C52; D41; D59; 330; present-day econometrics; formal econometrics; theory-data confrontation; bridge principles; applied econometrics